Analisa Pengaruh Kandungan Suspended Solid (SS) Air Baku Terhadap Kinerja Membran Mikrofiltrasi - Rony Riduan (Universitas Lambung Mangkurat, 2003)
Membrane for the production of potable water are becoming an increasingly viable alternative to conventional treatment trains. Membranes can produce water at a quality better than supplied by current traditional process. Microfiltration membranes can effectively remove turbidity, particles and suspended solids from raw water. Fouling by organics and turbidity on membranes can severely limit their potential usage with surface water resources. Fouling results in a flux decline, increased operating pressure and cleaning frequency.The purpose of this study is to assess the membrane performance based on flux and rejection capacity. Suspended Solid concentration clearly effects the flux decline but not significantly effects rejection capacity. Other parameters like operating pressure and acidity effect the optimum condition of membrane operation.